2004
DOI: 10.1016/j.bcp.2003.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of mitochondria during tocotrienol-induced apoptosis in MDA-MB-231 human breast cancer cells

Abstract: Tocotrienols, which are Vitamin E isoforms, are known to inhibit the growth of human breast cancer cells due partly to apoptosis. However, the characterization of tocotrienol-induced apoptosis is incomplete, particularly what happens during the initiation phase that precedes execution of the cells. The objective of this study was to clarify the apoptotic effects of tocotrienols, with especial emphasis in determining if the mitochondria-mediated death pathway is activated when human breast cancer cells are incu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
96
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(107 citation statements)
references
References 40 publications
10
96
1
Order By: Relevance
“…T3 has been shown to mediate its activity against a variety of chronic diseases, including cardiovascular diseases, neurologic diseases, diabetes, and cancer (9)(10)(11)(12)(13)(14). T3s have shown anticancer activity against cancers such as colon, breast, liver, lung, kidney, prostate, skin, and other cancers both in vitro (15)(16)(17)(18)(19)(20) and in vivo (21)(22)(23)(24)(25). T3 has the potency to induce apoptosis in a variety of cancer cell types (types 1-5).…”
Section: Introductionmentioning
confidence: 99%
“…T3 has been shown to mediate its activity against a variety of chronic diseases, including cardiovascular diseases, neurologic diseases, diabetes, and cancer (9)(10)(11)(12)(13)(14). T3s have shown anticancer activity against cancers such as colon, breast, liver, lung, kidney, prostate, skin, and other cancers both in vitro (15)(16)(17)(18)(19)(20) and in vivo (21)(22)(23)(24)(25). T3 has the potency to induce apoptosis in a variety of cancer cell types (types 1-5).…”
Section: Introductionmentioning
confidence: 99%
“…More recent work has demonstrated that cell cycle inhibition by T3 occurs through the control of the Rb/cdk4/ cyclin D pathway (Elangovan et al 2008) that is also affected by the HM forms of tocopherols, and particularly by c-TOH (Betti et al 2006). In the same cell models, T3 were demonstrated to induce apoptosis with d-T3 as the most potent form (Yu et al 1999) and with a mechanism that involves mitochondrial disruption and cyt c release (Takahashi and Loo 2004). As introduced above, recent studies by our group confirmed that d-T3 is the most potent T3 form with pro-apoptotic activity higher than a-TOS in breast cancer cells (Table 1) .…”
Section: Metabolite Formation and Activitymentioning
confidence: 65%
“…35 The anticancer effect of T3 was found to be mediated through antiproliferation, 16,36,37 induction of apoptosis, 38,39 cell cycle arrest, 13,40 antiangiogenesis 41 and antiinvasion. 18 More recently, c-T3, one of the four isoforms of T3, was reported to possess chemosensitizing effects, 17,18 which led us to speculate that c-T3 may be able to target the chemoresistant cancer stem-like cells.…”
Section: Discussionmentioning
confidence: 99%